Macrochirality of Self-Assembled and Co-assembled Supramolecular Structures of a Pair of Enantiomeric Peptides - Guo, Zhen; Song, Yongshun; Wang, Yujiao; Tan, Tingyuan; Ji, Yuwen; Zhang, Guangxu; Hu, Jun; Zhang, Yi (Frontiers in Molecular Biosciences, 2021)
Although macrochirality of peptides’ supramolecular structures has been found to play important roles in biological activities, how macrochirality is determined by the molecular chirality of the constituted amino acids is still unclear. Here, two chiral peptides, Ac-LKLHLHLQLKLLLVLFLFLALK-NH2 (KK-11) and Ac-DKDHDHDQDKDLDVDFDFDADK-NH2 (KKd-11), which were composed entirely of either L- or D-amino acids, were designed for studying the chiral characteristics of the supramolecular microstructures. It was found that monocomponent KK-11 or KKd-11 self-assembled into right- or left-handed helical nanofibrils, respectively. However, when they co-assembled with concentration ratios varied from 1:9 to 9:1, achiral nanowire-like structures were formed. Both circular dichroism and Fourier transform infrared spectra indicated that the secondary structures changed when the peptides co-assembled. MD simulations indicated that, KK-11 or KKd-11 exhibited a strong propensity to self-assemble into right-handed or left-handed nanofibrils, respectively. However, when KK-11 and KKd-11 were both presented in a solution, they had a higher probability to co-assemble instead of self-sort. MD simulations also indicated that, in their mixtures, they formed nanowires without handedness feature, a good agreement with experimental observation. Our results shed light on the molecular mechanisms of the macrochirality of peptide supramolecular microstructures.